Oligomeric Hydrogels Self‐Assembled from Reduction‐Controlled Condensation1. Issue 12 (28th January 2015) - Liu, Shuang; Tang, Anming; Xie, Maolin; Zhao, Yundan; Jiang, Jun; Liang, Gaolin
Abstract: Polymer hydrogels and small‐molecule‐based (SMB) supramolecular hydrogels have been widely explored. But oligomeric hydrogels have remained a challenge because synthetic difficulties of the oligomers and control of their amphiphilicities. Reported herein is the rational design of two precursors Cys(SEt)‐Lys‐CBT (1 ) and (Cys‐Lys‐CBT)2 (2 ) (CBT=2‐cyano‐6‐aminobenzothiazole) and the use of a biocompatible condensation to prepare oligomeric hydrogels. Glutathione reduction of1 or2 yields the same gelator Cys‐Lys‐CBT (3 ) which condenses with each other to yield amphiphilic cyclic oligomers. The oligomers instantly self‐assemble into nanofibers and form oligomeric hydrogels with similar mechanic properties. Chemical analyses indicated that the major condensation product in both two hydrogels is a cyclic dimer. Considering its biocompatibility, optimal mechanical strength, and biodegradability, we believe that our oligomeric hydrogel might be useful for long‐term drug delivery in the future. Abstract : Bowl full of gel : A biocompatible condensation reaction was employed to synthesize amphiphilic macrocyclized oligomers, which instantly self‐assembled into nanofibers through parallel stacking and formed oligomeric hydrogels.